Science Applications Using Solar System Macromedia FlashMX, Swift 3D and Swishmax - Elly Agustina Julisawati (Majalah SIKOMTEK, 2005)
Until now we know the fruit of nine planets that circulate around the sun through specificpathways called the orbit or elliptical orbit. The planets orbit around the sun because ofgravity or the gravitational force of the sun and this is what binds the planets remain in orbit.The order of the planets from closest to the sun are: Mercury, Venus, Earth, Mars, Jupiter,Saturn, Uranus and Pluto.Multimedia applications that provides three-dimensional images with forms like Swift 3Dand an application example that presents images such as Flash and swish animation that canprovide or produce an interactive application that can be expressed as in the form of